Extração em ponto nuvem para a determinação de benzo(a)pireno em água potável por espectrometria de fluorescência molecular - Silva, Marden Eugênio de Oliveira (2017)
Benz(a)pyrene (B(a)P) is part of the group of pollutants known as polycyclic aromatic hydrocarbons (PAHs). This compound is of great environmental interest because it is the most potent carcinogen among the 16 PAHs considered as priority by the United States Environmental Protection Agency (US-EPA). In this work, a method for the determination of B(a)P in drinking water by the cloud point extraction technique based on micellar medium formed by sodium dodecyl sulfate (SDS) as a process prior to molecular fluorescence spectrometry is proposed. The excitation conditions of B(a)P were previously evaluated to obtain fluorescence spectra with the highest possible intensity. The effect of the amount of SDS on the fluorescence emission of B(a)P was studied. Another study carried out was the stability of B(a)P over nine consecutive weeks, and it was observed that this compound was stable, since there were no variations of analytical signal in the time interval studied. The wavelength of 286 nm for the analyte excitation was chosen, with a maximum emission signal being recorded at 405 nm, whereas among the SDS concentrations for the cloud point procedure evaluated (0.5% to 4, 3%), that of 1% m v-1 corresponded to the highest emission signal of the analyte. The linear response range studied was between 1 and 110 µg L-1 with LOD and LOQ of 0.12 µg L1 and 0.37 µg L-1, respectively. The values obtained by the analysis of variance showed that the constructed linear model presents regression significance and is well adjusted. For the recovery tests, three levels of analytical curve concentrations were used, recoveries of 80 to 123% were obtained and the improvement factor presented value of 21. Finally, the proposed method was used for the determination of B(a)P in 10 drinking water samples from different districts of the city of João Pessoa. The presence of B (a) P was not detected in any of the analyzed samples, being in compliance with the current legislation which determines a maximum allowed value of 0.7 µg L-1.